2023
DOI: 10.1186/s13045-023-01456-y
|View full text |Cite
|
Sign up to set email alerts
|

The artificial intelligence and machine learning in lung cancer immunotherapy

Abstract: Since the past decades, more lung cancer patients have been experiencing lasting benefits from immunotherapy. It is imperative to accurately and intelligently select appropriate patients for immunotherapy or predict the immunotherapy efficacy. In recent years, machine learning (ML)-based artificial intelligence (AI) was developed in the area of medical-industrial convergence. AI can help model and predict medical information. A growing number of studies have combined radiology, pathology, genomics, proteomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 81 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…Lung cancer is one of the most frequently diagnosed cancers and the leading cause of cancer-related death worldwide [ 1 3 ], with lung adenocarcinoma (LUAD) representing the most common subtype of all diagnoses [ 4 , 5 ]. Early-stage LUAD can be cured by radical resection, but there is currently no curative treatment for patients with late-stage LUAD, despite the recent progression in molecularly targeted therapy, immunotherapy, and combinatorial therapy [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is one of the most frequently diagnosed cancers and the leading cause of cancer-related death worldwide [ 1 3 ], with lung adenocarcinoma (LUAD) representing the most common subtype of all diagnoses [ 4 , 5 ]. Early-stage LUAD can be cured by radical resection, but there is currently no curative treatment for patients with late-stage LUAD, despite the recent progression in molecularly targeted therapy, immunotherapy, and combinatorial therapy [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This includes research progress in areas such as predicting responses to targeted therapy in breast cancer and prognosis prediction of glioma [ 16 , 17 ]. Meanwhile, a growing number of studies have combined genomics, radiology, proteomics data, and pathology to estimate PD-L1 expression levels, TMB, and tumor microenvironment (TME) or predict the response to immunotherapy and side effects in patients with cancer [ 18 20 ]. Recent studies reported that a machine learning analysis of circulating immune cell characteristics or CT images in patients with NSCLC could be used to predict immunotherapy benefits [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these challenges, there is great hope for expanding treatment strategies targeting TME, including depletion or "reprogramming" of cancer promoting host cells in TME; Intervention measures to modify extracellular matrix (ECM), matrix components, and extracellular vesicles (EVs); Cell based therapies and vaccines; And immune checkpoint inhibitors. Moreover, integrating multiple cancer model data and advanced computational analysis, including artificial intelligence, has the potential to adopt a comprehensive system level approach about analyzing and integrating all the complexities of TME to identify key nodes [ 145 ]. In addition, significant advances in bioengineering will provide a platform for large-scale testing, such as in ex vivo organoids and tissue slices that accurately recurrent organ specific TMEs [ 146 148 ].…”
Section: Introductionmentioning
confidence: 99%